Integrated approach for estimating climate change impacts on CO2 sink capacity of inland waterbodies using hydrodynamic modelling and GIS analysis - Hanady H. Khalil; Mohamed A. Abdrabo; Mahmoud A. Hassaan; Mohamed M. Elshemy (Scientific Reports)
Abstract As one of their key regulatory ecosystem functions, inland lakes serve as CO2 sinks. The CO2 sink capacity of inland lakes depends on their water temperature and salinity as well as their water volume which are all highly sensitive to climate conditions. This paper aims to quantitatively estimate the change in the CO2 sink capacity of Wadi El-Rayan Lakes under climate change scenarios. For this purpose, an integrated approach combining CO2 solubility modelling, hydrodynamic simulations (Delft3D-FLOW) and GIS analysis was employed. According to the developed approach, CO2 solubility under variable temperature and salinity is mathematically modelled and this model is further used with the developed hydrodynamic model data for Wadi El-Rayan Lakes (temperature, salinity and water depth) to estimate their CO2 sink capacities. CO2 sink capacity is estimated for 2014 and 2050 under two Representative Concentration Pathways (RCPs) 2.6 and 8.5. Afterwards, the alteration in CO2 sink capacities due to climate change is determined using the modified hydrodynamic model. The results revealed that by 2050, the lakes would lose about 23–25% of their capacities compared to that of 2014 according to RCP 2.6 and 8.5, respectively.